2021
DOI: 10.3390/biology10050393
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Winter Water Temperature and Food Composition by the Copepod Cyclops vicinus (Uljanin, 1875) to Provide a Temporal Refuge from Fish Predation

Abstract: Frequent predation induces various defense strategies in prey, including morphological changes or migration patterns in zooplankton. We hypothesized that the winter dominance of Cyclops vicinus in the Upo Wetlands, South Korea, is an evolved temporal defense mechanism to avoid fish predation. Long-term data (2014–2019) showed that fish consumed the most cyclopoid copepods from spring to autumn. Lepomis macrochirus preferentially consumed C. vicinus; thus, C. vicinus density was lower from spring to autumn. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Our identification of the interrelationship between the major biological communities of the two tributary streams (Jiseok Stream and Hampyeong Stream) by stable isotope analysis revealed that the influence of P. clarkii on native organisms was minimal. The carbon isotope concentration consumed by predators was approximately 1‰ and the nitrogen isotope concentration consumed was different (around 3–5‰) from food source of predators [ 32 , 33 ]. Procambarus clarkii did not consume the available food sources (e.g., planktonic algae, periphyton, and cladocerans) collected in this study and clarkii was not consumed by other predators ( L. macrochirus and M. salmoides ).…”
Section: Discussionmentioning
confidence: 99%
“…Our identification of the interrelationship between the major biological communities of the two tributary streams (Jiseok Stream and Hampyeong Stream) by stable isotope analysis revealed that the influence of P. clarkii on native organisms was minimal. The carbon isotope concentration consumed by predators was approximately 1‰ and the nitrogen isotope concentration consumed was different (around 3–5‰) from food source of predators [ 32 , 33 ]. Procambarus clarkii did not consume the available food sources (e.g., planktonic algae, periphyton, and cladocerans) collected in this study and clarkii was not consumed by other predators ( L. macrochirus and M. salmoides ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the tendency of Rhodomonas sp. to dominate during periods of low water temperatures in temperate regions [50,51]. This also suggests that Rhodomonas sp.…”
Section: Cca Of the Phytoplankton Community And Environmental Factors...mentioning
confidence: 98%